Seasonal variation of pest mite populations in relation to citrus scion cultivars in northeastern Brazil (2017)
Pest populations in a given agroecosystem may be influenced by several abiotic and biotic variables, including the host plant cultivar. We compared the population fluctuation of pest mites in twenty citrus scion cultivars grafted on Rangpur lime (Citrus limonia). Adults of citrus rust mite Phyllocoptruta oleivora (Acari: Eriophyidae), Texas citrus mite Eutetranychus banksi and Tetranychus mexicanus (Acari:Tetranychidae) were monthly counted in each scion cultivar from April 2011 to February 2013 in Sergipe state, northeastern Brazil. Larger E. banksi population peak was recorded on sweet orange ‘Valência Montemorellos’ in February 2012 compared to the other cultivars and larger populations of T. mexicanus were found on sweet orange ‘Lima’ in January 2013 in comparison to acid limes ‘Tahiti IAC 5’ and ‘IAC 5-1’. The population of P. oleivora, however was not different among scion cultivars and varied only with time. Abiotic and biotic variables were important mechanisms underlying such responses. We conclude that the abundances of the mites E. banksi and T. mexicanus were influenced by scion cultivars only in some periods, suggesting putative resistance mechanisms in some genotypes to these pests.